The N-Acetylmuramic Acid 6-Phosphate Phosphatase MupP Completes the Pseudomonas Peptidoglycan Recycling Pathway Leading to Intrinsic Fosfomycin Resistance - Marina Borisova (American Society for Microbiology, 2017)
ABSTRACT Bacterial cells are encased in and stabilized by a netlike peptidoglycan (PGN) cell wall that undergoes turnover during bacterial growth. PGN turnover fragments are frequently salvaged by the cells via a pathway referred to as PGN recycling. Two different routes for the recycling of the cell wall sugar N-acetylmuramic acid (MurNAc) have been recognized in bacteria. In Escherichia coli and related enterobacteria, as well as in most Gram-positive bacteria, MurNAc is recovered via a catabolic route requiring a MurNAc 6-phosphate etherase (MurQ in E. coli) enzyme. However, many Gram-negative bacteria, including Pseudomonas species, lack a MurQ ortholog and use an alternative, anabolic recycling route that bypasses the de novo biosynthesis of uridyldiphosphate (UDP)-MurNAc, the first committed precursor of PGN. Bacteria featuring the latter pathway become intrinsically resistant to the antibiotic fosfomycin, which targets the de novo biosynthesis of UDP-MurNAc. We report here the identification and characterization of a phosphatase enzyme, named MupP, that had been predicted to complete the anabolic recycling pathway of Pseudomonas species but has remained unknown so far. It belongs to the large haloacid dehalogenase family of phosphatases and specifically converts MurNAc 6-phosphate to MurNAc. A ΔmupP mutant of Pseudomonas putida was highly susceptible to fosfomycin, accumulated large amounts of MurNAc 6-phosphate, and showed lower levels of UDP-MurNAc than wild-type cells, altogether consistent with a role for MupP in the anabolic PGN recycling route and as a determinant of intrinsic resistance to fosfomycin. IMPORTANCE Many Gram-negative bacteria, but not E. coli, make use of a cell wall salvage pathway that contributes to the pool of UDP-MurNAc, the first committed precursor of cell wall synthesis in bacteria. This salvage pathway is of particular interest because it confers intrinsic resistance to the antibiotic fosfomycin, which blocks de novo UDP-MurNAc biosynthesis. Here we identified and characterized a previously missing enzyme within the salvage pathway, the MurNAc 6-phosphate phosphatase MupP of P. putida. MupP, together with the other enzymes of the anabolic recycling pathway, AnmK, AmgK, and MurU, yields UDP-MurNAc, renders bacteria intrinsically resistant to fosfomycin, and thus may serve as a novel drug target for antimicrobial therapy.